2015
DOI: 10.3389/fpls.2015.01155
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations in CsMLO1 Confer Durable Powdery Mildew Resistance in Cucumber (Cucumis sativus L.)

Abstract: Powdery mildew (PM) is a serious fungal disease of cucumber worldwide. The identification of resistance genes is very important for resistance breeding to ensure cucumber production. Here, natural loss-of-function mutations at an MLO homologous locus, CsMLO1, were found to confer durable PM resistance in cucumber. CsMLO1 encoded a cell membrane protein, was mainly expressed in leaves and cotyledons, and was up-regulated by PM at the early stage of host–pathogen interaction. Ectopic expression of CsMLO1 rescued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 55 publications
(123 reference statements)
6
65
0
Order By: Relevance
“…The frequency distributions of DI indicated that PM resistance of cucumber were controlled by multiple loci (Fig. 2), which is consistent with previous studies [7,14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The frequency distributions of DI indicated that PM resistance of cucumber were controlled by multiple loci (Fig. 2), which is consistent with previous studies [7,14].…”
Section: Discussionsupporting
confidence: 91%
“…Most of the QTLs showed recessive inheritance, indicating that the resistance is governed by loss-offunction mutant alleles of certain susceptible genes [12,13]. Indeed, a mutant allele of the cucumber susceptibility gene CsaMLO8 (named as CsMLO1 in [14] explains the contribution to PM resistance by the QTL pm5.1 [15]. Except for the pm5.1, causal genes of other mapped QTLs for PM resistance in cucumber have not been discovered yet.…”
Section: Introductionmentioning
confidence: 99%
“…A prime example of the lossof-susceptibility mechanism is the barley mlo (mildew locus o) gene that encodes a defective, integral membrane protein which is important for infection of the powdery mildew pathogen (B€ uschges et al, 1997;Humphry et al, 2006Humphry et al, , 2010. The mlomediated powdery mildew resistance has been found in wheat, grapevine, rice, tomato and cucumber (Elliott et al, 2002;Bai et al, 2008;Nie et al, 2015;Pessina et al, 2016;Acevedo-Garcia et al, 2017). The wheat Lr34, Lr67 and Yr36 also belong to the loss-of-susceptibility R genes.…”
Section: Introductionmentioning
confidence: 99%
“…Podosphaera xanthii is the plant pathogen belonging to Erysiphaceae family, and the fungal belonging to this family cause the powdery mildew disease in most cultivated plants/ crops, particularly, P. xanthii is the pathogen for cucurbits (Mart ınez-Cruz et al 2018). In Korea, this fungus effects various crops in cucurbits, such as melon (Hong et al 2018), cucumber (Nie et al 2015), and other weed-like plants, such as Cirsium japonicum (Lee 2012). This powdery mildew pathogens have specific molecular mechanism called haustoria, which is used to invade the host cells (Lee 2012;Hong et al 2018).…”
mentioning
confidence: 99%
“…This powdery mildew pathogens have specific molecular mechanism called haustoria, which is used to invade the host cells (Lee 2012;Hong et al 2018). This fungus mostly cause serious economic loss in greenhouse environment, which decide the yield of the most cucurbits (Nie et al 2015).…”
mentioning
confidence: 99%